Missed Clinical Opportunities: Provider Recommendations for HPV Vaccination for 11-12 Year Old Girls is Limited - Vadaparampil, Susan T. (2011)
OBJECTIVE: The purpose of this study was to determine the prevalence of physician recommendation of human papillomavirus (HPV) vaccination in early (ages 11-12), middle (13-17), and late adolescent/young adult (18-26) female patients by physician specialty, and to identify factors associated with recommendation in early adolescents. METHODS: A 38-item survey was conducted April 2009 through August 2009 among a nationally representative random sample of 1,538 Family Physicians, Pediatricians, and Obstetricians and Gynecologists obtained from the American Medical Association Physician Masterfile. A multivariable model was used to assess factors associated with frequency of physician recommendation of HPV vaccination (“always”=76-100% of the time vs. other=0-75%) within the past 12 months. RESULTS: Completed surveys were received from 1,013 physicians, including 500 Family Physicians, 287 Pediatricians, and 226 Obstetricians and Gynecologists (response rate = 67.8%). Across the specialties, 34.6% of physicians reported they “always” recommend the HPV vaccine to early adolescents, 52.7% to middle adolescents, and 50.2% to late adolescents/young adults. The likelihood of “always” recommending the HPV vaccine was highest among Pediatricians for all age groups (P < .001). Physician specialty, age, ethnicity, reported barriers, and Vaccines for Children provider status were significantly associated with “always” recommending HPV vaccination for early adolescents. CONCLUSIONS: Findings suggest missed clinical opportunities for HPV vaccination, and perceived barriers to vaccination may drive decisions about recommendation. Results suggest the need for age and specialty targeted practice and policy level interventions to increase HPV vaccination among US females.